On the transfer of stratospheric ozone into the troposphere near the North Pole - Oltmans, Samuel J.; Raatz, Wolfgang E.; Komhyr, Walter D. (1989)
A series of nearly daily ozone vertical profiles obtained at station T-3 on Fletcher's Ice Island (about 85 deg N, about 90 deg W) during the period January-March 1971 shows several significant ozone intrusions into the troposphere. These intrusions are not only associated with enhanced ozone amounts in the stratosphere but also require tropopause folding events to transport ozone into the troposphere. These folds in the arctic tropopause appear to be capable of contributing significantly to the ozone budget of the arctic troposphere during the late winter and spring seasons. The importance of tropopause folding for bringing ozone into the troposphere seen in the daily ozone profiles confirms the results found in the Arctic Gas and Aerosol Sampling Program aircraft flights.